2016
DOI: 10.4103/0976-9668.175021
|View full text |Cite
|
Sign up to set email alerts
|

A hospital-based study on knowledge and attitude related to vitiligo among adults visiting a tertiary health facility of central India

Abstract: Background:Vitiligo is one of the common stigmatizing dermatosis in the Indian society and the vitiligo patients have to face significant psychological hurt and social neglect. The severity of the stigma is related to the society's attitude and knowledge about it.Aims and Objectives:To document the prevalent knowledge and attitude in general public towards vitiligo patients, and to identify the determinants of good/poor knowledge and attitude.Materials and Methods:A systematic random sampling technique was ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 13 publications
4
23
0
Order By: Relevance
“…ese findings were also supported by Asati and his colleagues [23]. Besides, the majority of the respondents recognized that vitiligo is more prevalent and exaggerated with exposure to psychological stress.…”
Section: Discussionsupporting
confidence: 68%
“…ese findings were also supported by Asati and his colleagues [23]. Besides, the majority of the respondents recognized that vitiligo is more prevalent and exaggerated with exposure to psychological stress.…”
Section: Discussionsupporting
confidence: 68%
“…A sizeable respondents still have a negative attitude towards vitiligo patients by avoiding shaking hands with a them (53.8). The overall attitude was comparatively poor which resembles same as a hospital-based study conducted by C.M Gupta et al 6 on knowledge and attitude related to vitiligo among adults visiting a tertiary health facility of central India.…”
Section: Discussionsupporting
confidence: 60%
“…Our results are fairly supporting Alshahrani findings, where the majority (84.3%) of our sample didn't consider vitiligo as a killer disease. In our study, of all the population (44.4%) thought that the disease is exaggerated by stress and anxiety, while only (21.6%) recognized it as an autoimmune indings regarding the existence of a treatment and the association with a special type of food are quite similar to what is [17] have indicated generally poor scores for attitudes, and good scores for the While they could not find any significant association between knowledge and attitude, in our study, negative attitudes were strongly associated with poor knowledge. The significance was highest with those who think that gecko and its saliva are causing vitiligo; value=0.003), eat food -value=0.001), value0.010), marry a value=0.006), and would stare value 0.042).…”
Section: Graph 4 Percentages Regarding Attitudes Toward Vitiligosupporting
confidence: 60%
“…Asati et al [17] have indicated generally poor scores for attitudes, and good scores for the knowledge. While they could not find any significant association between knowledge and attitude, in our study, negative attitudes were strongly associated with poor knowledge.…”
Section: Graph 4 Percentages Regarding Attitudes Toward Vitiligomentioning
confidence: 95%
See 1 more Smart Citation